2019
DOI: 10.1101/767830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-time dynamics of Plasmodium NDC80 reveals unusual modes of chromosome segregation during parasite proliferation

Abstract: Eukaryotic cell proliferation requires chromosome replication and precise segregation, followed by cell division, to ensure daughter cells have identical genomic copies. The kinetochore is a multi-protein structure assembled on chromosome centromeres, which mediates attachment to spindle microtubules and chromosome segregation during mitosis. Plasmodium spp., the causative agent of malaria, undergoes closed mitosis with an intact nuclear membrane and intranuclear mitotic spindle. However, the regulation of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 65 publications
5
27
0
Order By: Relevance
“…5B). This mirrors what has been seen in electron microscopy studies: nuclear spindles radiate from the nuclear poles, with attached kinetochores within an intact nuclear membrane during oocyst development [30,32].…”
Section: Pbkinesin-5-gfp Exhibits Multiple Nuclear Foci During Oocystsupporting
confidence: 78%
See 4 more Smart Citations
“…5B). This mirrors what has been seen in electron microscopy studies: nuclear spindles radiate from the nuclear poles, with attached kinetochores within an intact nuclear membrane during oocyst development [30,32].…”
Section: Pbkinesin-5-gfp Exhibits Multiple Nuclear Foci During Oocystsupporting
confidence: 78%
“…4D). This result showed that kinesin-5 distribution and localization is associated with spindle dynamics, similar to the behaviour of NDC80 [32], and can be blocked by taxol treatment, which binds tubulin and stabilises MTs by preventing depolymerisation (Fig. 4D).…”
Section: Spatiotemporal Dynamics Of Pbkinesin-5 Reveal Its Location Osupporting
confidence: 63%
See 3 more Smart Citations